Did We Forget Something? Fathering Supports and Programs in Prisons in Victoria, Australia - Bartlett, Tess S. (International journal of offender therapy and comparative criminology, 2019)
This article draws from data gathered for an Australian Research Council-funded study conducted in Victoria and New South Wales between 2011 and 2015, which examined how dependent children are responded to when their primary carer is imprisoned. In particular, this article specifically addresses a gap in knowledge by examining the current state of fathering programs in prison in Victoria. To do so, the views of 39 primary carer fathers incarcerated in Victoria are analysed. We argue that there is a distinct lack of support for fathers in prison, acting as a barrier towards maintaining father-child relationships. Findings indicate that 79% of the fathers in this study were never offered any parenting support services or programs. By clearly highlighting the state of fathering programs in prisons in Victoria, this article offers suggestions as to how best to facilitate the connection between incarcerated fathers and their children.